Globalization and the emergence of a transnational oligarchy - Elise S. Brezis (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The aim of this paper is to examine the evolution of recruitment of elites due to globalization. In the last century, the main change that occurred in the way the Western world trained its elites is that meritocracy became the basis for their recruitment. Although meritocratic selection should result in the best being chosen, we show that meritocratic recruitment may actually lead to class stratification and auto-recruitment. In this paper, I show that due to globalization, the stratification effect will be even stronger. Globalization will bring about the formation of an international technocratic elite with its own culture, norms, ethos, and identity, as well as its private clubs like the Davos World Economic Forum. We face the emergence of a transnational oligarchy.
Keywords: I21; O15; O40; 330; globalization; education; elites; meritocracy; recruitment; social mobility; Globalisierung; Bildung; Elite; Technokratie; Oligarchie; Personalbeschaffung; Soziale Mobilität; Wirtschaftliche Macht